Effects of Microbial-Mineral Interactions on Organic Carbon Stabilization in a Ponderosa Pine Root Zone: A Micro-Scale Approach - Dohnalkova, Alice C.; Tfaily, Malak M.; Chu, Rosalie K.; Smith, A. Peyton; Brislawn, Colin J.; Varga, Tamas; Crump, Alex R.; Kovarik, Libor; Thomashow, Linda S.; Harsh, James B.; Keller, C. Kent; Balogh-Brunstad, Zsuzsanna (Frontiers in Earth Science, 2022)
Soil microbial communities affect the formation of micro-scale organo-mineral associations where complex processes, including aggregate formation, microbial mineral weathering and soil organic matter stabilization occur in a narrow zone of biogeochemical gradients. Here we designed a field study to examine carbon stabilization mechanisms using in-growth mesh bags containing biotite that were placed in a ponderosa pine rhizosphere for 6 months and compared the content of the mesh bags to the surrounding bulk soil. We sought to determine the composition of the microbial community in the mesh bags compared to the surrounding soils, analyze the direct interactions between microbes and biotite, and finally identify the nature of the newly formed organo-mineral associations within the mesh-bags. Our results revealed that minerals in the mesh bags were colonized by a microbial community that produced organic matter in situ. The 16S rRNA gene sequencing and ITS2 region characterization revealed a phylogenetic similarity between the mesh bag and bulk soil archaea/bacteria and fungi microbiomes, with significant differences in alpha- and beta-diversity and species abundances. Organic carbon pools of the mesh bags, analyzed by Fourier transform ion cyclotron resonance mass spectrometry, contained lipid-like and unsaturated hydrocarbons while the bulk soil was comprised of lignin-like and carboxyl‐rich alicyclic molecules. These results support the in-situ formation of organic compounds by microbes in the mesh bags which strongly adhered to mineral surfaces. These strongly adhered organic compounds facilitated aggregation of mineral particles and were stabilized as organo-mineral assemblies forming "nanocrusts" on biotite surfaces, documented by high-resolution electron microscopy. Elemental depletion was also observed at the microbe-mineral interface by nano-scale chemical analysis that indicated mineral cations biogenically released from the biotite. Overall, this study elucidated the direct and indirect involvement of rhizospheric microbial communities in the formation of organo-mineral associations, soil organic carbon stabilization, and mineral weathering at micro- and nano-scales.